The Effect of Principal Transformational Leadership on Teacher Job Satisfaction: A Literature Review - Restiani, Berti; Hariri, Hasan; Rini, Riswanti (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
Transformational leadership is closely associated with important and positive work attitudes, particularly job satisfaction. In the school context, this means that principals need to act as leaders who use transformational styles to improve educational outcomes through teacher job satisfaction to improve outcomes in education through teacher job satisfaction. In Indonesia, empirical research on the effect of transformational leadership on the level of teacher job satisfaction. Thus, this article aims to explore the influence of transformational leadership on teacher job satisfaction. This research uses the literature review method by reviewing national and international journal articles from Google Scholar, focusing on articles published from 2018 to 2024. There were 28 articles used as references.  The review conducted shows that transformational leadership leadership has a significant effect on the level of job satisfaction of teachers job satisfaction. This article is expected to enrich theoretical knowledge about the influence of transformational leadership on teacher job satisfaction and become a reference for further research.